Cultured Trash, Not Trash Culture - Taufiqurrohman Taufiqurrohman; Setyo Utomo; Purwo Adi Wibowo (Universitas PGRI Semarang, 2017)
As civilized creature, human actually can manage trash as well as possible although it is often stereotyped as a vain thing. This article gives the proof that trash can be cultured as well so that a society can take benefits from the existence of it. This article parses ways of orderly managing it at schools, in this case two schools in Jepara. The results say that trash can be cultured by having an organization to manage the Trash Bank at schools and to train students to classify and recycle trash then take advantage of it by selling the collected and the recycled trash. It makes trash have good transformation of values, repelling against the prior stereotype. Finally, by taking example from Trash Bank management at schools, human can have so cultured trash that they would not be trapped by trash culture.